Reflexology and cancer - Ahmet Unlu; Onder Kirca; Mustafa Ozdogan (Journal of Oncological Sciences, 2018)
Reflexology is a complementary alternative medicine procedure carried out by applying pressure to specific points located mostly in the feet (sometimes in the hands), with intent to provide relief from certain symptoms. In reflexology thought to have a history of approximately 5000 years, it is believed that specific points in the feet are linked to certain organs and systems in the body, through energy channels, and that applying pressure to these points provides relief in the relevant organ and system, as well. However, no evidence has yet to be found that proves the alleged connections and mechanisms of reflexology. Indeed, studies carried out up to date were focused on the symptomatic effects of reflexology, rather than such links and mechanisms. In some studies, certain positive results have been obtained especially in terms of pain and anxiety. However, these studies were methodologically incomplete, as well, due to challenges such as the difficulty in creating blinding and placebo effect. As a result, currently we have no reliable evidence about the use of reflexology in any clinical situation. Nevertheless, when it is considered to be a safe procedure in terms of unwanted effects, it can be provided to patients as a supportive care service. Keywords: Reflexology, Cancer, Alternative medicine, Complementary medicine